Újragondolt istenkép - FERENCZI, Andrea (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2021)
God’s Image Revisited. God said to Moses, “I am who I am” (Exodus 3,14). Although Christian churches seek to present the New Testaments’ image of God, the loving, caring, and merciful God, yet the idea of a punitive, strict, and fearsome God lives stronger in many. Our image of God not only determines the nature of our rela-tionship with God, but it also influences our personality, actions, self-concept, mindset, and social relations. It acts within and through us. Although everyone has an image of God – regardless of whether one is a believer or not –, how we experience God’s relation to us is manifold. But why do we experience God’s re-lationship with us in so many ways? What circumstances shape and influence our image of God? It is not unusual that even believers of the same congregation give accounts of diverse images of God. Why? These questions are answered by calling upon psychological insights.